Ibn Taymiyya on Universals: Nominalism, Textual Hermeneutics, and the Question of Scientific Rationality - Teddy Yusuf; Dadang Sudana; Muhammad Zaka Al Farisi; Aceng Ruhendi Saifullah; Nur Ainiyah (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2026)
It is frequently asserted that Ibn Taymiyya's (d. 728/1328) denial of extramental universals commits him to an anti-abstractionist literalism and, ultimately, to hostility toward scientific rationality. This article argues that the assertion rests on a conflation of three logically independent theses — a metaphysical thesis about universals, a hermeneutical thesis about textual meaning, and an epistemological thesis about the sources of knowledge — and that once these are disentangled, the inference to antagonism toward science does not follow. Working from al-Radd ʿalā al-Manṭiqiyyīn and Darʾ Taʿāruḍ al-ʿAql wa al-Naql, and using conceptual analysis together with a historically disciplined philosophical hermeneutics, the study advances three findings. First, Ibn Taymiyya's position on universals is better described as a moderate conceptualism than as radical nominalism, and on the narrow question of the universal's mode of existence it stands closer to Avicenna than is usually recognised. Second, his critique of the syllogism is driven by an epistemological preference for sense, experience, and reasoning from particulars; he is therefore a defender of induction rather than its opponent, and the widespread characterisation of him as anti-inductive inverts his actual position. Third, and consequently, the genuine difficulty in his thought is not hostility to empirical inquiry but a justification gap: having denied that shared natures exist extramentally, he lacks a metaphysical warrant for the inductive generalisations upon which he himself relies — a difficulty he shares with the empiricist tradition from Hume onward. Reframing the problem in this way is more faithful to the texts and relocates Ibn Taymiyya from the position of an adversary of science to that of an early participant in a problem internal to empiricism itself.